Association of GCK gene DNA methylation with the risk of clopidogrel resistance in acute coronary syndrome patients. Issue 2 (11th October 2019) - Su, Jia; Zheng, Nan; Li, Zhenwei; Huangfu, Ning; Mei, Li; Xu, Xiaolei; Zhang, Li; Chen, Xiaomin
Abstract: Backgrounds: Clopidogrel resistance (CR), which was manifested as the failure of platelet inhibition in clopidogrel treatment, was likely to lead to cardiovascular events. Our study was aimed to explore the contribution of DNA methylation in glucokinase ( GCK ) to the CR risk. Methods: Among 36 CR and 36 non‐CR acute coronary syndrome (ACS) patients, the platelet functions were evaluated by VerifyNow P2Y12 assay (turbidimetric‐based optical detection) and DNA methylation levels on two fragments of the CGI from the GCK were investigated through bisulfite pyrosequencing methods. In addition, the GCK mRNA expression was analyzed via quantitative real‐time PCR. Lastly, the logistic regression was employed to test the interaction between GCK methylation and nongenetic variables in CR patients. Results: Subunit analysis showed that in male patients without DM but suffering from dyslipidemia, the increased methylation of cg18492943 indicated a risk of poor clopidogrel response (male, NCR vs CR(%): 84.86 ± 6.29 vs 88.16 ± 4.32, P = .032; without DM, NCR vs CR (%): 84.66 ± 6.18 vs 88.16 ± 4.17, P = .029; and dyslipidemia, NCR vs CR (%): 83.81 ± 6.96 vs 88.39 ± 4.74, P = .042).In addition, GCK mRNA expression was reduced in CR patients without DM. Moreover, regression analysis indicated that the values of platelet distribution width (PDW), total cholesterol (TC), and uric acid (UA) were correlated with the incidence of CR, and hypertension lowered the CR risk. Conclusions: A higher methylation of cg18492943 in GCK gene would lower the expression of GCK mRNA, which might contribute to CR in patients without DM. Meanwhile, PDW and TC might be risk factors in CR.